1978
DOI: 10.1093/neurosurgery/25.cn_suppl_1.174
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the Cervical Spine

Abstract: This has been a review of some of the movements of the cervical spine. Much data remain to be accumulated and certainly much work must be done to evaluate the effect of forces in various directions upon these movements. Perhaps an improved understanding of these movements in association with an understanding of the pathogenesis of disc degeneration will enable us to better understand the development of spondylosis. Most important this review uncovers the fallacy of laying the blame for the development of cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Cervical spine kinematics are commonly assessed using static, end-range of motion radiographs collected with the head in full flexion and full extension[1-5]. Previous studies have demonstrated significant inter-subject variability in intervertebral flexion-extension range of motion (ROM), ranging from 20% to 60% of the overall motion at each motion segment[4-8].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical spine kinematics are commonly assessed using static, end-range of motion radiographs collected with the head in full flexion and full extension[1-5]. Previous studies have demonstrated significant inter-subject variability in intervertebral flexion-extension range of motion (ROM), ranging from 20% to 60% of the overall motion at each motion segment[4-8].…”
Section: Introductionmentioning
confidence: 99%
“…Intervertebral range of motion (ROM) is commonly determined in vivo using two-dimensional lateral radiographs, typically acquired at static full-flexion and full-extension positions 7,23–25 . These measurements have inherent limitations, including the high measurement variability associated with manual digitization 23,24,26,27 , the absence of dynamic loading, and the inability to assess motion out of the film plane.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements have inherent limitations, including the high measurement variability associated with manual digitization 23,24,26,27 , the absence of dynamic loading, and the inability to assess motion out of the film plane. In order to improve our understanding of cervical spine kinematics, it has been suggested that three-dimensional (3D) measurements 7,28–32 be acquired during in vivo dynamic loading conditions 7,33–35 . An additional limitation of previous research has been the failure to assess the effects of arthrodesis on midrange kinematics, which make up the vast majority of activities of daily living 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed arthrodesis may lead to increased motion in adjacent vertebrae, resulting in overload [2][3][4][5][6] that leads to degeneration [4,[7][8][9][10][11][12] and potentially additional surgery [10,[13][14][15][16]. In an attempt to eliminate or minimize adjacent segment overload, several motion-preserving disk replacement devices have been recently developed [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%